TERAPI INHALASI SEDERHANA MENGGUNAKAN MINYAK KAYU PUTIH PADA PASIEN ISPA - Heltty, Heltty; Yati, Mimi; Risky, Sartini; Marhanto, Eka Dharma Putra; Lolok, Nikeherpianti; Juliansyah, Risky; Ramadan, Muhamad Fitrah (Sekolah Tinggi Ilmu Keperawatan Muhammadiyah Pontianak, 2024)
ARIs is an infectious disease of the upper or lower respiratory tract that can cause a variety of illnesses ranging from mild infections to severe, life-threatening illnesses, depending on the causative pathogen. Deaths due to ARIs were 10 to 50 times more common in developing countries than in developed countries. The aim of this research was to find out whether simple inhalation therapy using eucalyptus oil can prevent acute respiratory infections. In this research, researchers used descriptive methods. The descriptive method is a method for describing the current situation of objects and based on phenomena and as it is without manipulation and the researcher analyzes the phenomenon. This research used a case study method and carries out a series of one group pretest-posttest designs. The results showed differences before and after administering simple inhalation therapy using eucalyptus oil and there were significant differences in people's understanding and knowledge regarding acute respiratory infections after carrying out the pre-test and post-test. The conclusion of this study was that giving simple inhalation therapy using eucalyptus oil can prevent symptoms of acute respiratory infections.